Wage Differentiation via Subsidised General Training - Steinar Holden; V. Bhaskar (Center for Economic Studies and ifo Institute (CESifo), 2003)
We provide a new explanation for why firms pay for general training in a competitive labor market. If firms are unable to tailor individual wages to ability, for informational or institutional reasons, they will pay for general training in order to attract better quality workers. The market provision of training may well exceed the first best level. Our explanation relies on wage compression within skill categories, while imperfect competition based explanations for firm subsidised general training rely on wage compression across skill categories.
Keywords: 330